Upholding the Best Interests of the Child Principle in Police Investigations of Child Sexual Violence Victims in Indonesia - Melian Sahara; Kayus Kayowuan Lewoleba (Al-Risalah, 2025)
Sexual violence against children is a serious crime with long-term effects, requiring legal proceedings that prioritize the interests of children as victims. This study aims to analyze the factors that hinder the realization of the principle of the best interests of the child in the investigation process and to formulate its ideal implementation. The method used is normative legal research with a legislative and case study approach, supplemented by empirical data through interviews with investigators from the South Jakarta Metro Police PPA Unit. The results of the study show that the main obstacles include a lack of understanding among investigators, limited support facilities, the absence of explicit technical SOPs, the influence of conservative culture, and low public legal awareness. This study offers novelty by filling the gap in research on the principle of the best interests of the child specifically for children who are victims of sexual violence, with a focus on the investigation process an aspect that has been more extensively discussed in the context of children as perpetrators or at the trial stage. The implications of this study emphasize the importance of harmonizing regulations, developing technical guidelines based on the protection of children and victims of sexual violence, and enhancing the capacity of law enforcement officials to ensure optimal protection